PUISI ANA KARYA NAZIK AL-MALA’IKAH (Analisis Semiotik Riffaterre) - Yulia Nasrul Latifi (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
The material object of this writing is Ana, written by Nazik al Mala’ikah, an Iraqi poet. The formal object is Riffaterre’s semiotics. In his theory, Michael Riffaterre introduces two level of reading, namely heuristic (a mimesis reading which is based upon dictionary meaning with ungrammatical characteristics) and retroactive or hermeneutic (the decoding-process reading, which searches for a model, matrix, and hypogram for acquiring the poetic unity). The result shows that the meaning of Ana in heuristic reading is still spreaded, separated, and unfocused. In retroactive or hermeneutic reading, potential hypogram has shown the ide that Ana is mysterious. The Model (the poetic monumental sentence) is ‘baqaytu sahimatan huna’ and ‘abqa usa’ilu’. The Matrix is ‘the essence of human being’ on philosophical perspective. The actual hypogram, that the matrix is based on, is the existentialist thought on human being. The characteristic of this ideology is its acceptance and confession of human being as an existence. Despite his confusion, Ana> says that he is a contributor, creator, and determiner of history.